Penerapan Metode DMAIC dalam Peningkatan Acceptance Rate untuk Ukuran Panjang Produk Bushing - Ho Hwi Chie; Ferdian Hartoyo; Yudha Yudhistira; Andry Chandra (Bina Nusantara University, 2012)
Bushing is one of the eminent product of PT Indokarlo Mighty. The company requires some suppliers of iron cutting services to continue providing high qualified raw materials. The quality is the accuracy of the intended length of the products which is able to meet the requirements of the requested length. The purpose of this study is to determine what factors caused the defect on the length of the products. In addition, it is objected to provide appropriate solutions to eliminate to the factors, so that the number of defected products can be reduced. This study uses the methodology of Six Sigma improvement models Define-Measure-Analyze-Improve-Control (DMAIC) to make improvements in the quality of services provided by PT Argatama Multi Agung, while the improvement phase uses Design of Experiment (DOE) to find the machine configuration that can produce the best quality products. A significant increase in sigma is obtained from the conducted research.